Thylakoidal membrane lipid composition and its reflex in protoplasmic drought tolerance and photosynthetic capacity of almond tree - Matos M.; Campos P.; Lauriano J.; Semedo J.; Matos A.; Lidon F. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Fourteen (five Portuguese and nine foreign) varieties from a collection of Prunus amygdalus, Batsch, grown in Quinta do Valongo (DRATM, Mirandela, Portugal) were studied in what concerns photosynthetic capacity (Amax), protoplasmic tolerance evaluated through electrolyte leakage (I per cent) under osmotic stress and thylakoids lipid composition. Significant differences were found as regards some parameters, namely A max, I per cent and total lipid content. Of the six varieties, which presented the highest Amax values (less or equal to 45 mmol per m2.s), four were Portuguese. The case of 'José Dias' was particularly interesting, a promising variety that presented an enhanced membrane tolerance to dehydration (lower I per cent) associated to higher lipid contents, namely galactolipids. Such features may be related to better photosynthetic performance and reflect a higher degree of adaptation.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)